Performance Modelling and Analysis of the Delay Aware Routing Metric in Cognitive Radio Ad Hoc Networks - Namanya, Anitta Patience; Pagna-Disso, Jules (IEEE, 2013)
Cognitive Radio Networks have been proposed to solve the problem of overcrowded unlicensed spectrum by using the cognitive ability built in software radios to utilise the underutilised licensed channel when the licensed users are not using it. Successful results from the research community have led to its application to wireless technologies like Ad Hoc networks due to their extensive advantages. Cognitive Radio Ad Hoc networks are a novel technology that will provide a solution to many communication challenges. This paper investigates the end-to-end performance modelling of a link using quality of service parameters; delay vs. link capacity while considering the factors of spectrum management and node mobility of two nodes in tandem representing a hop in Cognitive Radio Ad Hoc networks. We modelled spectrum management and node mobility using the pre-emptive resume priority M/G/1 queuing model and the gated node model respectively. We considered delay aware routing schemes; shortest queue and random probability routing and compared them with the analytical link-capacity for analysis. The study shows that already existing mathematical models can be used as close approximations to analyse the queuing models proposed for Cognitive Radio Ad Hoc Networks.
Keywords: MANET; Cognitive; CRAHN; Routing